Manejo del cáncer colorrectal en el embarazo - Reyna-Villasmil, Eduardo (2020)
Cancer during pregnancy has increased due to delayed motherhood and the known occurrence of age-dependent malignant tumors. With the increase in colorectal cancer diagnosed in young adults, the number of cases during pregnancy is likely to increase. Colorectal cancer is one of the 3 most common types of cancer in women, but the occurrence during pregnancy is rare and is associated with a large number of diagnostic and therapeutic challenges since the diagnosis is usually made in advanced stages. Besides, early diagnosis is difficult because the signs/symptoms (vomiting, constipation, anemia, rectorrhagia, pain and bloating) can simulate those observed during pregnancy. After diagnosis, the therapeutic plan must be established immediately, according to gestational age, by a multidisciplinary medical team. Doctors who care for pregnant women with colorectal cancer face two problems: the need for early maternal cancer treatment and timing of pregnancy termination. Professionals must become familiar with the challenges associated with systemic treatment, since antineoplastic treatment presents several unknowns for its use.